GCMS and LCMS analyses of phytochemical compound in methanolic extract of Piper betle leaves - Mohammad, Mardhiah; Mohd Azlan, Mawaddah (2019)
Natural resources especially plants give great opportunities for alternative treatment of many diseases. The interests in herbal or plant medicines have been increasing in recent years due to their efficacy and cost-effectiveness (Ekor, 2014). Piper betle L. or known as ‘Sireh’ in Malaysia has been useful in treating various conditions including wound injuries, conjunctivitis, constipation, bronchitis, and asthma (Hossain et al, 2017). Therefore, this study was aimed to investigate the phytochemical compounds present in Piper betle L. methanolic extraction using Gas Chromatography-Mass Spectrometry (GCMS) and Liquid Chromatography-Mass Spectrometry (LCMS) analyses. First, the leaves of the plant were grounded into powder and consecutively soaked in methanol for 15 days. The mixture was then filtered and converted to concentrate using rotary evaporator before been subjected to analyses. GCMS and LCMS have identified 10 and 26 compounds respectively. ‘Phenols’ was identified as a major component of the extract in both analyses. Additional compounds such as ‘Cassiaside’, ‘Samarcandin’ and ‘Sesamoside’ were identified by LCMS. The results exhibited compounds with medicinal properties such as antioxidant, anti-inflammatory, and anti-cancer properties. This study has discovered the presence of phytocomponents with therapeutic importance, which can further be studied and be used in future treatments.